Hemorrhage and thrombosis in acute leukemia (Hematology Meeting Reports, 2009)
Patients with acute leukaemias are at high risk of both hemorrhage and thrombosis. This risk is different according to: 1. the type of leukemia, i.e.: acute myeloblastic leukemia (AML), acute lymphoblastic leukemia (ALL), or acute promyelocytic leukemia (APL); and 2. the phase of treatment, i.e.: onset of the disease, remission induction, consolidation. Among bleeding complications, of particular importance is the disseminated intravascular coagulation (DIC) syndrome, due to the massive intravascular activation of blood coagulation with consumption of clotting factors and platelets, leading to severe haemorrhages. Thrombosis of large vessels is a more rare complication, although recent data indicate that it can be a relevant problem at the onset of AML, and during induction chemotherapy in ALL.